Query Cost-Reduction For Quranic-Arabic Information Retrieval Using Hexadecimal Conversion Algorithm - Mazlan, AA; Norwawi, NM; Ismail, R; Al Omoush, A; Fauziah Abdul Wahid (Univ Utari Malaysia-Uum, 2024)
Indexed by WOS